Investigation and Optimization for Performance Characteristics of Bump-type Foil Journal Bearings with Various Foil Materials - Vishal Mourya; Skylab P. Bhore (Tribology in Industry, 2022)
In this paper, the bump-type foil bearing is considered to analyze and optimize its performance characteristics with various foil materials. For the study, the operating parameters such as friction coefficient F1, F2 and loading pressure P are considered variable input parameters. The response surface methodology-based BBD model is used to design and analyze these variable parameters. The structural stiffness and equivalent stress of bump-type foil bearings are considered as the output responses in the present study. The multiobjective GRA technique is used to evaluate the optimum value of operating parameters for each foil material and compare its results. These results show that the loading pressure is the most influencing operating parameter on the output responses, followed by friction coefficient F1 and then F2. By the GRA technique, the Inconel X750 is found to be the most significant foil material, followed by Spring Steel EN42J for bump-type foil bearings. Moreover, it is also observed that the dissimilar foil material in bump-type foil bearings provides better results compared to similar foil material. The combination of stainless steel 316 (bump foil) and phosphor bronze (top foil) offers better results than similar foil results. In addition, the fabrication cost of bump-type foil bearings should be reduced with dissimilar foil materials.